2010
DOI: 10.1186/1471-2466-10-7
|View full text |Cite
|
Sign up to set email alerts
|

Different screening strategies (single or dual) for the diagnosis of suspected latent tuberculosis: a cost effectiveness analysis

Abstract: BackgroundPrevious health economic studies recommend either a dual screening strategy [tuberculin skin test (TST) followed by interferon-γ-release assay (IGRA)] or a single one [IGRA only] for latent tuberculosis infection (LTBI), the former largely based on claims that it is more cost-effective. We sought to examine that conclusion through the use of a model that accounts for the additional costs of adverse drug reactions and directly compares two commercially available versions of the IGRA: the Quantiferon-T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(109 citation statements)
references
References 40 publications
5
103
1
Order By: Relevance
“…In low-prevalence settings, the combination of TST and IGRA may be the best strategy. [51] Currently, there is little consensus on the most appropriate screening test in high-prevalence settings such as SA. [52] A patient due to commence biologic therapy should have a TST, an IGRA test (if deemed appropriate by the clinician), and a CXR.…”
Section: Screening For Ltbimentioning
confidence: 99%
“…In low-prevalence settings, the combination of TST and IGRA may be the best strategy. [51] Currently, there is little consensus on the most appropriate screening test in high-prevalence settings such as SA. [52] A patient due to commence biologic therapy should have a TST, an IGRA test (if deemed appropriate by the clinician), and a CXR.…”
Section: Screening For Ltbimentioning
confidence: 99%
“…In terms of cost, however, the TST appears best suited for the resource-strapped environment of Trinidad & Tobago (if the calculation of this variable is based mainly on the cost of the materials required to perform the test versus the cost of labor and other inputs). This argument is partly supported by Pooran et al, who concluded in a recent report that screening for LTBI using TST alone was the most cost-effective testing strategy but ultimately incurred the highest cost due to test inaccuracies [25]. Another factor that may make the TST less cost-effective over time is high replacement costs, since the Mantoux test solution is often not accessible in developing countries and would have to be replaced with the relatively labor-intensive IFN-release assay.…”
Section: Discussionmentioning
confidence: 90%
“…The combination of the TST and the QFT test could be an alternative way of improving diagnostic testing for LTBI (1,9,18,25). However, the TST itself has a poor sensitivity of 80% (17) and poor specificity among individuals vaccinated with BCG, which is the case for most HCW exposed to TB.…”
Section: Discussionmentioning
confidence: 99%